Acute appendicitis is associated with appendiceal microbiome changes including elevated Campylobacter jejuni levels. Issue 1 (3rd June 2020) - Oh, Sun Jung; Pimentel, Maya; Leite, Gabriela G S; Celly, Shreya; Villanueva-Millan, Maria Jesus; Lacsina, Isabela; Chuang, Brennan; Parodi, Gonzalo; Morales, Walter; Weitsman, Stacy; Singer-Englar, Tahli; Barlow, Gillian M; et al.
Abstract : Objectives: To compare the appendiceal microbiomes and examine the prevalence of Campylobacter species in the appendices of adult subjects with confirmed acute non-perforated appendicitis and controls with healthy appendices. Design: Archived samples of formalin-fixed paraffin-embedded appendiceal tissues were obtained from 50 consecutive female subjects who underwent appendectomy for acute, non-perforated appendicitis, and 35 consecutive female controls who underwent incidental appendectomy during gynaecological surgery. Results: 16S rRNA gene sequencing revealed that the relative abundances (RAs) of the major phyla in appendiceal tissues (Firmicutes, Proteobacteria, Bacteroidetes, and Actinobacteria) were similar in both groups. Beta diversity was significantly different due to differences in Bacteroidetes and Proteobacteria (p<0.0001). Within Proteobacteria, RAs of classes Alphaproteobacteria ( 21%, fold change (FC)=1.31, false discovery rate (FDR) p value=0.03) and Epsilonproteobacteria ( 1%, FC=0.25, FDR p value>0.05) were increased in acute appendicitis samples. RAs of unknown genera from families Burkholderiaceae and Enterobacteriaceae were decreased in appendicitis samples, and 14 genera were increased, including Neisseria, Acinetobacter and Campylobacter . Quantitative PCR revealed that levels of Campylobacter jejuni DNA, but not other Campylobacter species or pathogens tested, were significantly higher in appendicitis samples than in controls (p=0.013). Using a cut-off of 0.31 pg/µL, 40% of appendicitis cases and 6% of controls were positive for C. jejuni, indicating specificity of 93.7% (95% Cl 79.2 to 99.2), sensitivity of 40.9% (95% Cl 24.7 to 54.5), and OR of 10.38 (Fisher's p value=0.0006, 95% Cl 2.3 to 47.4). Conclusions: Our findings indicate that Campylobacter jejuni may be a significant cause of acute appendicitis. This supports earlier studies and suggests that targeted antibiotic therapies could be an alternative treatment for a subset of non-complicated acute appendicitis cases.